A Clinical Update in Interstitial Lung Disease 2017
DOI: 10.1136/thoraxjnl-2017-210983.301
|View full text |Cite
|
Sign up to set email alerts
|

P159 Preliminary experience of a tailored ild pulmonary rehabilitation program and inspiratory muscle training delivered in a hospice and home setting

Abstract: BackgroundDysponea, muscle wasting, and fatigue are common manifestations in interstitial lung disease (ILD). Pulmonary rehabilitation programmes (PRP) aim to improve symptoms and quality of life in ILD but research is very limited about the role and feasibility of inspiratory muscle training (IMT) in PRP.MethodsSix patients with a mixed disciplinary team diagnosis of ILD (5 males, median age 80 range 67–85) participated in a tailored PRP either in an IMT (n=3) or control group (n=3). PRP involved three days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Alquaimi M et al (2017) conducted a study on pulmonary rehabilitation program (PRP) in ILD patients. This study revealed that IMT in ILD patients improved 6MWD, Fatigue severity scale (FSS) and MIP 31. Kazuki Okura et al (2016) conducted a study on the efficacy of moderate-intensity, short-duration inspiratory muscle training in COPD patients.…”
mentioning
confidence: 93%
“…Alquaimi M et al (2017) conducted a study on pulmonary rehabilitation program (PRP) in ILD patients. This study revealed that IMT in ILD patients improved 6MWD, Fatigue severity scale (FSS) and MIP 31. Kazuki Okura et al (2016) conducted a study on the efficacy of moderate-intensity, short-duration inspiratory muscle training in COPD patients.…”
mentioning
confidence: 93%